2010
DOI: 10.1007/s12155-010-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feedstock Pretreatment Performance and Its Effect on Soluble Sugar Availability

Abstract: Cellulosic feedstocks for bioenergy differ in composition and processing requirements for efficient conversion to chemicals and fuels. This study discusses and compares the processing requirements for three lignocellulosic feedstocks-soybean hulls, wheat straw, and de-starched wheat bran. They were ground with a hammer mill to investigate how differences in composition and particle size affect the hydrolysis process. Enzyme hydrolysis was conducted using cellulase from Trichoderma reesei at 50°C and pH 5. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Analysis of variance (p = 0.05) showed that particle size did not have significant effect on the lignin content. This is consistent with the results of a study conducted by Lamsal & Madl (2011) that found that differences in particle sizes had not have significant effect on lignin content of wheat straw, wheat hull and soybean. On the other hand, the results of analysis of variance (p = 0.05) showed a significant effect of washing treatment on lignin content.…”
Section: Effects Of Physical Pretreatment and Washing Treatment On Chsupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of variance (p = 0.05) showed that particle size did not have significant effect on the lignin content. This is consistent with the results of a study conducted by Lamsal & Madl (2011) that found that differences in particle sizes had not have significant effect on lignin content of wheat straw, wheat hull and soybean. On the other hand, the results of analysis of variance (p = 0.05) showed a significant effect of washing treatment on lignin content.…”
Section: Effects Of Physical Pretreatment and Washing Treatment On Chsupporting
confidence: 92%
“…This made the hydrolysis process was running more intensively. This result was similar with the results reported by Lamsal & Madl (2011) who found that there was a correlation between particle size reduction and the increase of reducing sugars in soybean hulls, even though the higher cellulose content was in the biomass with larger particel size.…”
Section: Effects Of Physical Pretreatment On Enzymatic Hydrolisis Of supporting
confidence: 92%
“…Although a significant effort has been made to improve the pretreatment step, an efficient enzymatic hydrolysis still requires high enzyme loadings which contribute to the high costs of the biomass-derived ethanol [1,2]. Researchers attempted to reduce the cost of enzymatic hydrolysis [3,4] by (i) minimizing the costs of enzyme production, (ii) increasing the enzymes specific activity, (iii) reducing the required cellulase loading by pretreating the biomass [5], (iv) or recycling the enzymes for multiple rounds of hydrolysis [2,4,[6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This speeds its saccharification for subsequent bioethanol production by Saccharomyces cerevisae or other synergistic microbes (Garvey et al 2013). Sometimes used in concert with other heator chemical-based pretreatments (Lamsal, Madl, and Tasakpunidis 2011), Trichoderma reesei inoculation or enzyme injection has had successes against a very wide array of some of the world's most important bulky and saccharification-resistant agricultural wastes (Sarkar, Ghosh, and Bannerjee 2012), including corn stover (Minty et al 2013), wheat straw (Xin, Zhang, Downloaded by [University of Colorado -Health Science Library] at 10:52 14 October 2014 and Wong 2013), soybean straw (Xu et al 2007), rice straw and rice bran (Das et al 2013), wheat bran, and soybean hulls (Banerjee et al 2010). It has shown great promise in pretreatment of what is arguably the most-talkedabout energy crop today: switchgrass (Cianchetta et al 2012).…”
Section: Fungimentioning
confidence: 99%